Fr. Agustín de Vetancurt: The "Via crucis en mexicano". Issue 2 (27th March 2017) - Schwaller, John F.
Abstract : The reputation of Fr. Agustín de Vetancurt, one of the better known Franciscans of colonial Mexico, derives largely from his fame as a historian. He is the author of the monumental Teatro mexicano (1698), a historical description of the most important events of colonial New Spain. Fr. Agustín was also an accomplished scholar of Nahuatl, and published several works in that language. This essay will take a preliminary look at his life and times by focusing on a small work written by him in Nahuatl. It is a guide for the ceremony of the Stations of the Cross, celebrated throughout the year but especially on Good Friday.